BENIGN CYSTIC OVARIAN TERATOMA IN A CROSS BRED CATTLE - Kannan, Kavitha; I, Poornachandhar; M, Thangapandiyan; Sarath (The Indian Journal of Animal Reproduction, 2020)
The present study reports a case of benign cystic ovarian teratoma in a cross bred cow. A round mass of size 5×5.5×6 cm was found in the right ovary. The mass was firmly encapsulated with cartilaginous tissue and its cross section revealed tufts of hair matted in thick, dried, yellow sebaceous material. The histopathological investigation of the massconfirmed it as benign cystic teratoma. The teratoma was lined by well-differentiated stratifiedsquamous keratinized epithelium with scattered areas ofhair follicles andsebaceous glands.